Theorizing Adult Learning from the Postmodern Perspective: What Questions Do We Need to Ask? - Dae Joong Kang (Adult Education Research Conference, 2006)
The purpose of this roundtable paper is to pose a critique to adult learning theory building and to propose different questions to explore learning activities from the postmodern perspective.
Keywords: Adult learning theory; postmodernism